Cellulose Micro/Nanofibres of Merbau (Intsia bijuga) Waste: Effects of Chemical Treatments on Structural and Morphology Features - Razali, Nur Amira Mamat; Aziz, Fauziah Abdul; Rahman, Saadah Abdul (Chemic Publishing Company, 2017)
Cellulosic material derived from Merbau (Intsia bijuga) was isolated at atmospheric pressure. In the first stage, the samples were delignified using peroxyacetic acid to remove the amorphous structure. In the second stage, the samples were double-bleached using hydrogen peroxide and sodium hydroxide. The morphology of the cellulose samples was compared. From the X-ray diffraction (XRD) data, it is evident that both acid and alkali bleached celluloses have rich cellulose I structure.